Strengthening Students’ Soft Skills through a Structured Public Speaking Workshop among University and Senior High School Students in Central Aceh - Julia Noviani; Chairun Nisa; Wali Ara; Hafiz Mustaqim; Konadi Iwanada (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Public speaking is an essential soft skill supporting academic and professional development. However, many students experience anxiety, low self-confidence, and difficulty organizing ideas when speaking before an audience. This community service program aimed to strengthen public speaking skills among university students of IAIN Takengon and senior high school students in Central Aceh through a structured training workshop. The program involved 41 participants and was implemented through conceptual explanation, guided speaking practice, interactive engagement using Mentimeter, and reflective evaluation. Training materials were designed using Canva to ensure structured and visually clear delivery. Initial responses indicated nervousness, fear of making mistakes, and lack of confidence. After the workshop, the majority of participants reported improved understanding of speech structure, anxiety management strategies, and higher confidence levels .After the workshop, participants reported improved understanding of speech structure, anxiety management strategies, and higher confidence levels. Although the evaluation relied on self-reported perceptions within a single-session format, the findings suggest that structured, practice-oriented workshops can positively influence communicative readiness and serve as an effective starting point for strengthening public speaking confidence in educational settings.